Performance Achievements of Family Business through Successor Readiness and The Relationship between Family and Business Members - Gracia Ongkowijoyo; Timotius F.C.W Sutrisno; Teofilus Teofilus (Universitas Airlangga, 2020)
Family businesses are one of the biggest contributors to Indonesia’s gross domestic product (GDP). Universitas Ciputra facilitate their students with family business guild. Succession plan and communication are important aspects for family businesses. Family businesses must educate potential successors in order to implement the succession plan well. The purpose of this study was to examine the effect of preparation level of successors towards family business performance; examine the effect of relationships among family and business members towards family business performance. A quantitative approach was used with a population of Universitas Ciputra’s Family Business Community. Purposive random sampling technique was used, yeilding a total sample of 93 people. The data analysis method used is Partial Least Square (PLS). The results showed that preparation level of heirs variable has a positive and significant effect on family business performance; the relationship among family and business members variable has a positive and significant effect on family business performance.